Philosophy's violent sacred Heidegger and Nietzsche through mimetic theory - Armitage, Duane 1982- (East Lansing Michigan State University, 2021)
"This book critiques the postmodernism and Continental philosophy of Heidegger and Nietzche through the lens of the mimetic theory of Rene Girard"--
1. The sacred as violence -- 2. Nietzsche's religious hermeneutics -- 3. Heidegger's violent sacred -- 4. A Girardian critique of postmodernity.
Includes bibliographical references and index
Keywords: Girard, René -- 1923-2015; Nietzsche, Friedrich Wilhelm -- 1844-1900; Heidegger, Martin -- 1889-1976; Girard, Rene -- 1923-2015; Nietzsche, Friedrich Wilhelm - 1844-1900; Heidegger, Martin - 1889-1976; Girard, René - 1923-2015; Memetics; Mémétique; PHILOSOPHY / General; Memetics